Inside national health reform - McDonough, John E. (John Edward); Milbank Memorial Fund. (Berkeley : University of California Press ; New York : Milbank Memorial Fund, 2011)
This indispensable guide to the Affordable Care Act, our new national health care law, lends an insider's deep understanding of policy to a lively and absorbing account of the extraordinary--and extraordinarily ambitious--legislative effort to reform the nation's health care system. Dr. John E. McDonough, DPH, a health policy expert who served as an advisor to the late Senator Edward Kennedy, provides a vivid picture of the intense effort required to bring this legislation into law. McDonough clearly explains the ACA's inner workings, revealing the rich landscape of the issues, policies, and con.
The knowledge base : why national health reform? -- Social strategy : Massachusetts Avenue -- Political will I : prelude to a health reform campaign -- Political will II : a health reform campaign -- Title I : the three-legged stool -- Title II : Medicaid, CHIP, and the governors -- Title III : medical care, Medicare, and the cost curve -- Title IV : money, mammograms, and menus -- Title V : who will provide the care? -- Title VI : the stew -- Title VII : bio-similar biological products -- Title VIII : class act -- Title IX : paying for the ACA or about half of it -- Title X-plus : the manager's amendment and the reconciliation act.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Health care reform -- United States; Health care reform; Federal government; Medical care, Cost of; Politics, Practical; Health Care Reform; Federal Government; Health Care Costs; National Health Programs; Politics; United States; Services de santé -- Réforme -- États-Unis.; Services de santé -- Réforme.; Gouvernement fédéral.; Soins médicaux -- Coût.; Assurance-maladie.; Politique; federal government; politics; MEDICAL -- Health Risk Assessment; MEDICAL -- Health Policy; Politics, Practical; Medical care, Cost of; Federal government; Health care reform; United States